Do phosphoric acid esters affect the immediate enamel bond strengths?. Issue 22 (16th November 2016) - Xu, Jingqiu; Liang, Bing; Hoth-Hannig, Wiebke; Zhang, Ling; Jin, Xiaoting; Wang, Chaoyang; Fu, Baiping; Hannig, Matthias
Abstract: Purpose: To investigate the effects of phosphoric acid esters (PAEs)-containing primers on the micro-tensile bond strengths (MTBS) of etched enamel, the micro-morphologies of the resin–enamel interfaces, and the enamel surfaces. Materials and Methods: Thirty-three bovine incisors were used in this study. After the labial enamel surfaces were highly polished, they were etched, water sprayed, and air-dried. Afterward, the enamel surfaces were treated with or without (control) one of three PAEs-containing primers (40%MDP, Ivoclar Vivadent; Resulcin AquaPrime A + B, DMG; Xeno V, Dentsply), water sprayed, and air-dried. Subsequently, an adhesive Heliobond (Ivoclar Vivadent) was applied and resin composite (Core Build-up, Bisco) was placed incrementally. They were prepared into multiple beams of about 1 × 1 × 8 mm for MTBS tests. The enamel surfaces and resin–enamel interfaces were analyzed by SEM and TEM. The data were analyzed by two-way ANOVA and LSD test. Results: Using PAEs-containing primers could increase the enamel MTBS ( p < 0.05). The primer MDP produced higher MTBS than the primer Resulcin AquaPrime A + B and Xeno V. The SEM findings revealed the primed enamel surfaces were covered with a thin or glue-like layer of monomer-calcium salts of PAEs and the residual enamel crystallites, and various micro-porosities were detected within the hybrid layers. The TEM findings revealed the hydroxyapatite crystallites were tightly covered by the adhesive, the adhesive mixed with resin composite, or sparse irregular enamel crystallites. Conclusion: The application of PAEs-containing primers on the etched enamel substrate could significantly increase the immediate enamel bond strengths. However, this effect was dependent on the individual PAEs-containing primer used.